2019
DOI: 10.1093/ajcn/nqz009
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial to assess beverage hydration index in healthy older adults

Abstract: Background: The beverage hydration index (BHI) is a composite measure of fluid balance after consuming a test beverage relative to water. BHI is a relatively new measure that has been explored in young, but not yet older, adults. Objective: The aim of this study was to investigate potential differences in BHI between euhydrated younger and older adults after drinking 4 different commercial beverages. We hypothesized that 1) older subjects would remain in positive fluid balance longer than young subjects after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 35 publications
(58 reference statements)
5
26
1
Order By: Relevance
“…Findings from this study indicate that the consumption of Nuun electrolyte tablets with water can lead to improved fluid balance over the consumption of water alone in active individuals. This may be attributed to the electrolytes present within the Nuun solutions [ 5 , 14 , 15 ]. The 2 h BHI for 1× and 2× concentration Nuun electrolyte in water is similar to that previously reported for cola, and greater than that reported for items such as diet cola, sports drink, lager, coffee, and tea [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from this study indicate that the consumption of Nuun electrolyte tablets with water can lead to improved fluid balance over the consumption of water alone in active individuals. This may be attributed to the electrolytes present within the Nuun solutions [ 5 , 14 , 15 ]. The 2 h BHI for 1× and 2× concentration Nuun electrolyte in water is similar to that previously reported for cola, and greater than that reported for items such as diet cola, sports drink, lager, coffee, and tea [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those findings, compared to those of the present study, could be due to differences in the formulations of the two beverages, with Nuun having fewer carbohydrates and more electrolytes. Previous BHI research on differences between young and older adults found that increases in concentration of sodium, not amino acids or carbohydrates, resulted in greater hydration [ 15 ]. However, no significant differences were observed between the 1× and 2× concentrations of Nuun, suggesting that there may be a limit to what electrolyte levels are needed to improve fluid retention in a rested state.…”
Section: Discussionmentioning
confidence: 99%
“…Maughan et al [14] proposed the beverage hydration index (BHI) in 2016 as a measure of the hydrating capacity or efficacy of a given beverage relative to water. Since that time, BHI has been used to compare the hydration efficacy of a variety of beverages [14,18,19]. This index is able to assess how a beverage impacts post-ingestion body fluid balance in individuals independent of sex or body mass [19].…”
Section: Introductionmentioning
confidence: 99%
“…This measurement thereby enables comparisons of the hydration capacity of various beverages both within and across studies. Although the 2-h post-ingestion time point was proposed by Maughan as the standard for comparison [14], additional information can be gleaned from data throughout the entire 4-h testing period, especially for older adults [18,20] for whom ingested beverages are retained for a longer period of time, or after consumption of beverages that maintain positive fluid balance beyond 2 h.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation